Quality properties of whole milk powder on chicken breast emulsion-type sausage - Kyu-Min Kang; Sol-Hee Lee; Hack-Youn Kim (Journal of Animal Science and Technology, 2021)
The aim of the study was to determine the effect of whole milk powder (WMP) as heterologous proteins on chicken breast emulsion-type sausages. The quality properties of WMP on such chicken breast emulsion-type sausages were investigated by measuring the proximate composition, pH, color, cooking yield, protein solubility, and by applying other methods, such as texture profile analysis (TPA), microphotograph, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and electronic nose. The crude fat, protein, and ash contents of 15% WMP samples were significantly higher than the control samples (p < 0.05). The redness of the cooked samples significantly increased with an increase in the WMP contents (p < 0.05). The cooking yield of WMP treated samples was significantly higher than the control sample (p < 0.05). Additionally, the hardness, gumminess, and chewiness of WMP treated samples were significantly higher than the control sample (p < 0.05). The sarcoplasmic and myofibrillar proteins of samples containing 15% WMP were significantly higher than the control samples (p < 0.05). The result of SDS-PAGE showed that the C protein, sarcoplasmic protein, actin, and tropomyosin increased with an increase in the WMP contents. The principal component analysis plot of WMP-treated samples was clearly different from that of the control samples. Based on these results, it was predicted that WMP could be useful as heterologous protein on emulsion-type sausage.